Boys' Dormitory (1909)
Front elevation taken at angle from northwest; two students on porch; captioned 'Boys Dormitory.' (1 card has correspondence, to 'J.W. Spangler' of San Francisco; postmarked 1909; 'This is the new boys Dormitory [sic] Finished last Spring.' (built 1908])